Hypercalcaemic crisis in an elderly patient with pulmonary tuberculosis - Chan, Jason Yongsheng (Oxf Med Case Reports, 2015)
Tuberculosis is an uncommon but recognized cause of hypercalcaemia, though calcium levels are seldom severely elevated and rarely result in symptoms. In the elderly patient however, several competing aetiologies may contribute to hypercalcaemia and the diagnostic evaluation may be confounded by polypharmacy as well as multiple co-existing medical conditions. We present here a case of an elderly man who presented with pulmonary tuberculosis and concomitant delirium secondary to hypercalcaemic crisis. Treatment with anti-tuberculous drugs, together with supportive care, eventually led to resolution of hypercalcaemia and restoration of mental function.